Recent Advances in Biomass-Based Waste Materials for the Removal of Chromium (VI) from Wastewater: A Review - Rai, Rajan; Karki, Dirgha Raj; Bhattarai, Krishna Prasad; Pahari, Bishnu; Shrestha, Nabina; Adhikari, Sangita; Gautam, Surendra Kumar; Poudel, Bhoj Raj (Amrit Research Journal, 2021)
Hexavalent chromium (Cr(VI)) is a critical pollutant with high toxicity, even at trace concentrations. Cr(VI) is possibly carcinogenic and mutagenic and can produce serious health issues. Hence, it is necessary to remove Cr(VI) from the water before releasing it into the environment. Currently, numerous removal techniques were used. Adsorption is the best method compared to others because it is simple, cheap, highly efficient, and can be used in water having trace concentrations of contaminants. Biomass-based waste materials (BMWs) are found as far better adsorbents than commercially and other available adsorbents. In this study, the existing Cr(VI) removal techniques are reviewed and, a broad range of current research studies of Cr(VI) removal from water by using BMWs are evaluated. This review can be helpful to develop a more efficient, cheap, reliable, and environmentally benign bio-adsorbent. It is obvious after the literature review given herein that BMWs exhibited potential adsorbents for the removal of Cr(VI). Also, the chemically modified adsorbents exhibited a higher adsorption capacity than unmodified adsorbents.